Role of Streptococci as etiological agents of dental caries - Nishat Zafar; Ashiq Ali; Muhammad Yasir Afzal; Qaisar Tanveer; Sidra Bibi; Irha Basit; Huma Nasir; Shanzay Imtiaz; Usman Nazir (Novel Research in Microbiology Journal)
Dental plaques are notorious and lead to dental caries responsible for dental decay. Streptococci are the leading microorganisms associated with dental plaques. These are Gram-positive, normal microbial flora, nonmotile, non-spore forming, and facultative anaerobes. These include Alpha, Beta, and Gamma hemolytic species. Streptococcus sp. produces a high amount of lactic acid through the fermentation of sugars, causes lowering of the pH leading to the plaque formation around teeth, and serves as a biofilm. Microbial biofilm provides certain attachment sites for growth and colonization of other bacteria, and also causes resistance to the antimicrobial agents. These Streptococci can be transmitted to the infants through parents or caretakers' kiss. This mode of transmission is the key role for the contribution of S. mutans in dental caries. In Pakistan, a national survey was conducted in 1992 on tooth decay, which showed that two teeth per person were decayed, missing, or filled, thus becomes an alarming situation. Minimal knowledge related to tooth decay is observed in the clinical settings; however, no similar studies have been carried out in Pakistan.